Experimental Investigation Utilizing Thermal Image Technique to the Heat Transfer Enhancement Using Oscillated Fins (Journal of Engineering, 2013)
Heat transfer around a flat plate fin integrated with piezoelectric actuator used as oscillated fin in laminar flow has been studied experimentally utilizing thermal image camera. This study is performedfor fixed and oscillated single and triple fins. Different substrate-fin models have been tested, using fins of (35mm and 50mm) height, two sets of triple fins of (3mm and 6mm) spacing and three frequenciesapplied to piezoelectric actuator (5, 30 and 50HZ). All tests are carried out for (0.5 m/s and 3m/s) in subsonic open type wind tunnel to evaluate temperature distribution, local and average Nusselt number (Nu) along the fin. It is observed, that the heat transfer enhancement with oscillation is significant compared to without oscillation for low air inlet velocity. Higher thermal performance of triple fins is obtained compared to the single rectangular fin, also triple fins with (height=50mm and finspacing=3mm) gives better enhancement as compared to other cases. This work shows that the piezoelectric actuator when mounted on the rectangular fins shows great promise for enhancing the heat transfer rate.